EFEKTIVITAS PEMBELAJARAN INKLUSI BERBANTU HYPERMEDIA UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA SD DITINJAU DARI KELAS RENDAH DAN KELAS TINGGI - Rahma Dani, Esti Aulia; Kalifah, Fitria; Dwijayanti, Ida; Nailul Farichah, Rima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the implementation of hypermedia-assisted inclusive learning in lower and upper elementary grades, its contribution to teachers' professional competence, and its effectiveness in improving students' cognitive learning outcomes at SD Supriyadi Semarang. The research employed a mixed-methods approach with a one-group pretest-posttest pre-experimental design involving 27 students from Grade 2C and 28 students from Grade 4B. Data were collected through observations, documentation, reflective interviews, and learning tests, then analyzed using descriptive qualitative and inferential methods with the Wilcoxon Signed Rank Test. The findings revealed that hypermedia-assisted inclusive learning was effectively implemented in both grades through Universal Design for Learning (UDL) principles and contributed positively to teachers' pedagogical competence development. Classical mastery increased from 77.8% to 100% in Grade 2C and from 75.0% to 100% in Grade 4B, with Wilcoxon test significance values below 0.05 in both classes. These results confirm that hypermedia-assisted inclusive learning is effective in improving elementary school students' cognitive learning outcomes.